Digital violence in Mexican university couples: Analysis of its relationship with conflict over internet use and emotional skills - Huerta Mata, Rosa María; Marcos-Sánchez, Rafael; Díez González, María del Carmen (Journal of Technology and Science Education, 2026)
In today's digital environment, intimate relationships are developing new forms of domestic violence, namely digital violence through direct aggression and coercive digital control. This research aims to analyze the relationship between digital violence in Mexican university couples, interpersonal and intrapersonal conflicts over internet use, and emotional skills (attention, clarity, and repair), taking into account differences between men and women. The methodology used was a quantitative, cross-sectional, and correlational design. A total of 605 university students (410 women and 195 men) from the Actopan Higher School, Hidalgo, Mexico, participated. Participants completed three instruments: the Digital Abuse in Dating Questionnaire (CDAQ), the Internet-Related Experiences Questionnaire (CERI), and the TMMS-24 Scale on emotional skills. Nonparametric analyses, linear regression, and cluster analysis were applied. The results reveal significant correlations, differentiated by gender, between direct aggression and digital coercive control. Relationships between emotional skills and conflicts over internet use, differentiated by gender, were also found. Finally, it we found that intrapersonal conflict predicts direct aggression in women and digital coercive control in men, while for women, coercive control is predicted by interpersonal conflicts. In conclusion, greater digital literacy, further development of emotional skills, and preventive interventions are important for reducing digital violence in intimate relationships among university students.
Keywords: digital violence; direct aggression and coercive control; emotional skills; conflict internet use; university couples